2004
DOI: 10.1093/jnen/63.8.882
|View full text |Cite
|
Sign up to set email alerts
|

The Neurodegeneration Sequence in Prion Diseases: Evidence from Functional, Morphological and Ultrastructural Studies of the GABAergic System

Abstract: Loss of the GABAergic system of neurons has been reported to be the first detectable neuropathological change in prion diseases, which features the accumulation of an aberrant isoform of the prion protein (PrP(Sc)). To determine the timing of GABAergic system dysfunction and degeneration and its relationship to PrP(Sc) accumulation during the course of prion disease in Syrian hamsters, we applied 3 approaches: i) quantifying GABA-immunopositive neurons and their processes by light and electron microscopy to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
60
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 58 publications
12
60
0
Order By: Relevance
“…In earlier studies, we and others demonstrated the initial replication of prions at the site of injection with transport along axons (35,36). In the studies described here, PrP Sc formation was initiated by intrathalamic inoculation of prions, and presumably anterograde axonal transport of PrP Sc occurred along the monosynaptic thalamocortical system of axons that connects the thalamus with the cortex (1,6,37).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In earlier studies, we and others demonstrated the initial replication of prions at the site of injection with transport along axons (35,36). In the studies described here, PrP Sc formation was initiated by intrathalamic inoculation of prions, and presumably anterograde axonal transport of PrP Sc occurred along the monosynaptic thalamocortical system of axons that connects the thalamus with the cortex (1,6,37).…”
Section: Discussionsupporting
confidence: 53%
“…In prion-infected rodents, neurodegeneration begins with the accumulation of PrP Sc in neuronal membranes, followed by dendritic atrophy and loss and finally nerve cell death (1,4,10). During studies on the pathogenesis of experimental scrapie in mice, we found that the release of the Notch-1 intracellular domain transcription factor (NICD) preceded early dendritic atrophy in scrapie-infected mice (4).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…9,21,22 Animal models of CJD also demonstrate white matter deposition of PrP Sc , astrocytes, and vacuolization, all of which are hallmarks of CJD pathology, as well as damage to myelinated axons. 1,10,[23][24][25][26] Recently, new evidence is accumulating to suggest a fundamental relationship of the prion protein to WM. While predominantly neuronal, PrP C (the nor- mal cellular precursor protein) is also expressed in astrocytes and oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, synaptic disorganization and loss have been described in sporadic and inherited Creutzfeldt-Jakob disease, including cases associated with octapeptide insertions (31). Accumulation of abnormal PrP at presynaptic and postsynaptic sites has been found to precede neuronal dysfunction and death and be associated with loss of synaptic contacts in the CNS of scrapie-infected mice and patients with CreutzfeldtJakob disease (29,(32)(33)(34).…”
Section: Synaptic Dysfunction In Prion and Other Neurodegenerative DImentioning
confidence: 99%